La ricerca a fronte della sfida ambientale Materiali del III Seminario - ginelli, elisabetta (Scuole di dottorato, 2008)
La ricerca a fronte della sfida ambientale, the third volume in the DOTTA series, this publication documents the third edition of the Osdotta seminar co-ordinated by the Polytechnic of Milan, held in Lecco on 12-13-14 September 2007. The acronym of the Monitoring Centre of the Doctorate in Architectural Technology (Osservatorio del Dottorato in Tecnologia dell'Architettura), Osdotta was generated by the need to create a space for cultural exchange in relation to research contents and methods pertinent to technological disciplines. An experience acknowledged as a site of scientific interconnection and networked structure, it sets itself the goal of exploring the complexity of the research on multiple scales, investigating and focusing emerging issues and studying the national training scenario so as to boost the professional level of the research. The 2007 edition of the national seminar demonstrates the consolidation of an inter-site education/training experiment of an innovative character that materialises in the rendering of the results of exchange and dialogue on a theme with a wealth of faceted values: the environment, in the form of a challenge that explores the relation with technology.